Electrical and Thermal Characterisation of Millscale Modified Sn-Cu Lead-Free Solders - Sekunowo, Olatunde; Durowaye, Stephen; Fashakin, Gbenga (Journal of the Institute of Engineering, 2019)
Lead-free solders are gaining much attention as a result of legislation against the inclusion of lead and other hazardous materials in solders used in joining electronic components. This study investigated the effect of iron millscale (IMS) modified tin-copper (Sn-Cu) alloy on the electrical resistivity, electrical, and thermal conductivities of the solder samples under increasing applied current. The input materials consist of tin, zinc and iron millscale while the copper was varied from 0.2 – 1.0 wt. %. Fabrication of the alloy employed metal casting technique followed by relevant test samples preparation for characterisation in terms of microstructure, electrical, and thermal conductivities. Results show that the sample with 1 wt. % Cu addition exhibited the highest electrical and thermal conductivity values of 9967.9 S/m and 11.24 x 10-5 W/mK respectively at applied current value of 600 A with the lowest resistivity of 1 x 10-4 (Ωm). The solder alloy microstructure confirmed the presence of Cu6Sn5-FeO intermetallic phase dispersed in Sn matrix forming a continuous network. Contribution to the overall desirable performance of the solder alloy may have stemmed from the strong and coherent inter-crystal cohesion between the Cu6Sn3 and FeO phases which resulted in improved electrical and thermal conductivities of the as cast solder. The grade of solder alloy fabricated is adjudged suitable for assembling electronic components in industrial plant control panels.